Antifungal activity of the extracts and saponins from Sapindus saponaria L. - Tsuzuki,Joyce K. (2007)
Extracts from the dried pericarp of Sapindus saponaria L. (Sapindaceae) fruits were investigated for their antifungal activity against clinical isolates of yeasts Candida albicans and C. non-albicans from vaginal secretions of women with Vulvovaginal Candidiasis. Four clinical isolates of C. albicans, a single clinical isolated of each of the species C. parapsilosis, C. glabrata, C. tropicalis, and the strain of C. albicans ATCC 90028 were used. The hydroalcoholic extract was bioactivity-directed against a clinical isolate of C. parapsilosis, and showed strong activity. The n-BuOH extract and one fraction showed strong activity against all isolates tested. Further column-chromatography on silica gel separation of this fraction afforded two pure triterpene acetylated saponins: 3-O-(4-acetyl-beta-D-xylopyranosyl)-(1->3)-alpha-Lrhamnopyranosyl-(1->2)-alpha-L-arabinopyranosyl-hederagenin (1) and 3-O-(3,4-di-acetyl-beta-D-xylopyranosyl)-(1->3)-alpha-L-rhamnopyranosyl-(1->2)-alpha-L-arabynopyranosyl-hederagenin (2). The structures of the compounds were based on spectral data (¹H and 13C NMR, HSQC, HMBC and MS), and on with literature. The saponins isolated showed strong activity against C. parapsilosis.